Accuracy of Colon Capsule Endoscopy in Detecting Colorectal Polyps in Individuals with Familial Colorectal Cancer: Could We Avoid Colonoscopies?. (7th February 2017) - Alvarez-Urturi, Cristina; Fernández-Esparrach, Gloria; Ibáñez, Inés Ana; Rodríguez De Miguel, Cristina; Dedeu, Josep Maria; Bessa, Xavier; Córdova, Henry; Pellisé, Maria; Balaguer, Francesc; Ginés, Angels; Barranco, Luis; Araujo, Isis K.; et al.
Abstract : Background . Individuals with a family history of colorectal cancer (CRC) have an increased risk of CRC. We evaluated the diagnostic yield of CCE in the detection of lesions and also two different colon preparations. Methods . A prospective multicenter study was designed to assess CCE diagnostic yield in a cohort of asymptomatic individuals with a family history of CRC. CCE and colonoscopy were performed on the same day by 2 endoscopists who were blinded to the results of the other procedure. Results . Fifty-three participants were enrolled. The sensitivity, specificity, PPV, and NPV of CCE for detecting advanced adenomas were 100%, 98%, 67%, and 100%. Sensitivity, specificity, PPV, and NPV of CCE for the diagnosis of individuals with polyps were 87%, 97%, 93%, and 88%, respectively. CCE identify 100% of individuals with significant or advanced lesions. Overall cleanliness was adequate by 60.7% of them. The PEG-ascorbic boost seems to improve colon cleanliness, with similar colonic transit time. Conclusion . CCE is a promising tool, but it has to be considered as an alternative technique in this population in order to reduce the number of colonoscopies performed. More studies are needed to understand appropriate screening follow-up intervals and optimize the bowel preparation regimen.